2017
DOI: 10.1380/ejssnt.2017.127
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Oxygen Concentration of Si Wafer Surface in Si Emission on Nano Ordered Three-Dimensional Structure Devices

Abstract: In past studies, the Si emission phenomenon is one of the issues for fabrication of 3D structure devices such as FinFETs and Vertical MOSFETs. In this paper, it is found that novel Si emission phenomena depending on the surface oxygen concentration of Si wafer occur, when Si pillars patterned less than 100 nm are oxidized. A wafer with high oxygen concentration which is over 1.0×1018 atoms/cm 3 can suppress Si emission from the Si pillar compared to the low oxygen concentration wafers which are less than 1.0×1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…However, our experiments do not find any crystal defects such as dislocations, slips, or stacking faults. 10,11) In addition, our experiments observe local thinning of Si pillar during the oxidation. If a large amount of selfinterstitials surely diffuses through the Si pillar core, it should stop the local thinning by the Si regrowth at the interface.…”
Section: Si Missing Mechanismsupporting
confidence: 51%
See 1 more Smart Citation
“…However, our experiments do not find any crystal defects such as dislocations, slips, or stacking faults. 10,11) In addition, our experiments observe local thinning of Si pillar during the oxidation. If a large amount of selfinterstitials surely diffuses through the Si pillar core, it should stop the local thinning by the Si regrowth at the interface.…”
Section: Si Missing Mechanismsupporting
confidence: 51%
“…[5][6][7][8][9] We also observe quite similar phenomena experimentally. 10,11) These unique phenomena for the oxidation of 3D structures are thought to come from several reasons. In silicon oxidation, it is known that Si is emitted from the interface into the oxide as well as into the silicon substrate.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that Si missing and self-limiting occur during the oxidation process of nanopillars. 72,73) The oxidized pillars have thinner diameters than those expected from simple conversion from Si into SiO 2 . The oxidation stops after a while and shows selflimitation.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that such strain leads to the unconventional growth of Si oxide film. 4,5) The strain induced in the oxide film could also have an unconventional effect on the film reliability such as dielectric breakdown. Previous studies have reported that the dielectric breakdown of the oxide film is triggered by O-vacancy (V O )-related defects in the film.…”
Section: Introductionmentioning
confidence: 99%